Relationship between pupil to limbus diameter ratio with blood pressure and pulse rate in young adults: An observational study - Himanshu Sharma; Ishrat Khan; Varsha Porwal; Haneef Khan (Asian Journal of Medical Sciences, 2024)
Background: Autonomic function tests play a crucial role in the diagnosis and prognosis of clinical conditions. Although there are multiple autonomic function tests available, there is still a need for rapid and less expensive tests for the benefit of the general population. The pupil-to-limbus diameter (PLD) ratio is one such test that is simple and cost-effective. It uses the principle of pupil dilation and constriction due to the influence of the autonomic neurons’ activity. Aims and Objectives: The present study aimed to observe a correlation between PLD ratio with blood pressure and pulse rate in young adults. Materials and Methods: The present study was conducted at the Department of Physiology, Jhalawar Medical College, Jhalawar. The present study was an observational study conducted among 1st-year medical students in the age group of 18–24 years. PLD ratio was measured by the two-box method as described in the literature. After providing 3–5 min of rest, blood pressure and pulse were recorded in the right arm in the sitting position by a digital blood pressure monitor. Results: Positive correlation was observed between the PLD ratio of right eye and pulse rate (r=0.9696). There is a weak negative correlation exists between the PLD ratio of right eye and systolic blood pressure (r value=−0.3802). Conclusion: The study concludes that the PLD ratio correlates with autonomic activity. However, there is a need for a study with large population to confirm the correlation. Furthermore, there is a study to assess the autonomic responses in female participants in different phases of menstrual cycle.